Exploration of Experience-Based Marketing Strategies in Building Customer Engagement and Improving Retention: A Case Study in the Tourism and Travel Industry - Gatot Wijayanto; Ana Fitriyatul Bilgies; Yutiandry Rivai; Rovanita Rama; Arini Novandalina (Dinasti International Journal of Education Management And Social Science, 2024)
This article explores the efficacy of experience-based marketing strategies in enhancing customer engagement and retention within the dynamic landscape of the tourism and travel industry. Drawing upon a comprehensive case study analysis, this research delves into the nuanced mechanisms through which experiential marketing initiatives impact consumer behavior and loyalty. By examining diverse experiential tactics such as immersive storytelling, interactive technology integration, and personalized service offerings, this study uncovers the pivotal role of memorable experiences in fostering emotional connections and long-term relationships with customers. The findings underscore the significance of crafting unique, sensory-rich encounters that resonate with travelers' aspirations, preferences, and values. Moreover, this research elucidates the strategic implications of leveraging experiential marketing to differentiate brands, drive word-of-mouth advocacy, and sustain competitive advantage in an increasingly crowded marketplace. Insights from this study offer actionable recommendations for tourism and travel businesses to design and implement effective experience-based marketing campaigns that cultivate deep-seated connections with their target audience, engender brand loyalty, and ultimately drive business growth.